A hypermorphic IκBα mutation is associated with autosomal dominant anhidrotic ectodermal dysplasia and T cell immunodeficiency - Courtois, Gilles (American Society for Clinical Investigation, 2003)
X-linked anhidrotic ectodermal dysplasia with immunodeficiency (XL-EDA-ID) is caused by hypomorphic mutations in the gene encoding NEMO/IKKγ, the regulatory subunit of the IκB kinase (IKK) complex. IKK normally phosphorylates the IκB-inhibitors of NF-κB at specific serine residues, thereby promoting their ubiquitination and degradation by the proteasome. This allows NF-κB complexes to translocate into the nucleus where they activate their target genes. Here, we describe an autosomal-dominant (AD) form of EDA-ID associated with a heterozygous missense mutation at serine 32 of IκBα. This mutation is gain-of-function, as it enhances the inhibitory capacity of IκBα by preventing its phosphorylation and degradation, and results in impaired NF-κB activation. The developmental, immunologic, and infectious phenotypes associated with hypomorphic NEMO and hypermorphic IKBA mutations largely overlap and include EDA, impaired cellular responses to ligands of TIR (TLR-ligands, IL-1β, and IL-18), and TNFR (TNF-α, LTα1/β2, and CD154) superfamily members and severe bacterial diseases. However, AD-EDA-ID but not XL-EDA-ID is associated with a severe and unique T cell immunodeficiency. Despite a marked blood lymphocytosis, there are no detectable memory T cells in vivo, and naive T cells do not respond to CD3-TCR activation in vitro. Our report highlights both the diversity of genotypes associated with EDA-ID and the diversity of immunologic phenotypes associated with mutations in different components of the NF-κB signaling pathway.